Room-temperature fabrication of SiC microwire photodetectors on rigid and flexible substrates via femtosecond laser direct writing. Issue 45 (17th November 2020) - Liang, Shuyu; Dai, Yunzhi; Wang, Gong; Xia, Hong; Zhao, Jihong
Abstract : Herein, a rapid and eco-friendly method for the fabrication of SiC microwires on rigid or flexible substrates is reported.  Via  the use of FsLDW, SiC nanoparticles dispersed in a liquid environment are assembled into a single microwire to prepare a high-performance PD. Abstract : Flexible ultraviolet (UV) photodetectors (PDs) have gained increasing demand because of their widespread applications in wearable devices. However, difficulties associated with complicated fabrication technologies significantly limit their scope of application. Herein, via the development of a femtosecond laser direct writing (FsLDW) strategy, silicon carbide (SiC) nanoparticles are found to be assembled in a single microwire within 30 s. The surface of the deposited SiC microwire presents a three-dimensional porous structure, which is conducive to improving the responsivity of the device. The responsivity of a SiC-based microwire PD to UV light at 365 nm is found to be 55.89 A W −1 at a 1 V bias. The as-fabricated SiC microwire PDs on a glass substrate exhibit thermal stability at 350 °C, and the response speed of the PDs becomes notably faster at high temperatures, suggesting their promising applications in harsh conditions. Due to the low-temperature processing characteristics of this process, they can be prepared not only on glass substrates, but also on thermosensitive polymer substrates without an extra transfer process. Moreover, the SiC microwires prepared via FsLDW are directly deposited on the flexible substrate, and the prepared flexible SiC-based PDs can still work stably after being bent 2000 times. This research unveils a feasible way to fabricate a PD with excellent thermal stability and mechanical flexibility.